Model Pendidikan Agama Kristen Berwawasan Majemuk dalam Membina Sikap Toleransi Beragama di Indonesia - Fredik Melkias Boiliu; Desetina Harefa; Haposan Simanjuntak; Septerianus Waruwu; Irfan F. Simanjuntak (Sekolah Tinggi Alkitab Jember, 2021)
This article discusses the model of Christian religious education with a compound insight in fostering religious tolerance in Indonesia. In the context of nationhood, society and religion in Indonesia according to the basis of Pancasila, there are six recognized religions, namely Islam, Christianity, Catholicism, Hinduism, Buddhism and Confucianism. Religious differences are supposed to acknowledge each other, respect each other, and cooperate in virtue. But in fact differences in religious beliefs become a driving factor to bring down, demean each other, or mix between religions with each other. Therefore, there needs to be a diverse religious insight in fostering religious tolerance in Indonesia. Therefore, the model of Christian religious education is inclusive, multicultural, dialogue and peaceful as the right approach to foster religious tolerance in daily life. This research uses a method of literature study that refers to concepts and theories according to literature available such as articles published in various scientific journals, books and other scientific papers.AbstrakArtikel ini membahas tentang model pendidikan agama Kristen berwawasan majemuk dalam membina sikap toleransi beragama di Indonesia. Dalam konteks berbangsa, bermasyarakat dan beragama di Indonesia sesuai dasar Pancasila, ada enam agama yang diakui yaitu Islam, Kristen, Katolik, Hindu, Budha dan Konghucu. Perbedaan agama seharusnya untuk saling mengakui, saling menghormati, dan bekerja sama dalam kebajikan. Namun pada faktanya perbedaan keyakinan agama menjadi faktor pendorong untuk saling menjatuhkan, saling merendahkan, atau mencampuradukkan antar agama yang satu dengan yang lain. Oleh sebab itu, perlu adanya wawasan agama yang mejemuk dalam membina sikap toleransi beragama di Indonesia. Untuk itu, model pendidikan agama Kristen yang inklusif, multikultural, dialog dan damai sebagai pendekatan yang tepat untuk membina sikap toleransi beragama dalam kehidupan sehari-hari. Penelitian ini menggunakan metode kajian pustaka yang merujuk pada konsep dan teori sesuai literature yang tersedia seperti artikel-artikel yang dipublikasikan dalam berbagai jurnal ilmiah, buku-buku dan makalah ilmiah lainya.